SELF-EFFICACY AND ACHIEVEMENT MOTIVATION ON STUDENT LEARNING INDEPENDENCE - Miranda, Vania; Faslah, Roni; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This research was conducted with the aim of examining the effect of self-efficacy and achievement with independent learning on students of the Faculty of Economics, State University of Jakarta. This research is using a questionnaire method. The respondent selection technique used Proportional Stratified Random Sampling in order to obtain a sample of 165 respondents from students of the Office Administration Education study program. Data was collected by distributing questionnaires using a Likert scale. Results based on the research conducted, it was found that self-efficacy has a positive and significant effect on Self-Regulated Learning. Achievement motivation has a positive and significant effect on Self-Regulated Learning. Self-Efficacy and Achievement Motivation have a positive and significant effect on Self-Regulated Learning.